Luminescent Strategies for Label‐Free G‐Quadruplex‐Based Enzyme Activity Sensing. Issue 11 (3rd May 2017) - Ma, Dik‐Lung; Dong, Zhen‐Zhen; Vellaisamy, Kasipandi; Cheung, Ka‐Man; Yang, Guanjun; Leung, Chung‐Hang
Abstract: By catalyzing highly specific and tightly controlled chemical reactions, enzymes are essential to maintaining normal cellular physiology. However, aberrant enzymatic activity can be linked to the pathogenesis of various diseases. Therefore, the unusual activity of particular enzymes can represent testable biomarkers for the diagnosis or screening of certain diseases. In recent years, G‐quadruplex‐based platforms have attracted wide attention for the monitoring of enzymatic activities. In this Personal Account, we discuss our group's works on the development of G‐quadruplex‐based sensing system for enzyme activities by using mainly iridium(III) complexes as luminescent label‐free probes. These studies showcase the versatility of the G‐quadruplex for developing assays for a variety of different enzymes. Abstract : This Personal Accounts describes our group's recent efforts in the development of G‐quadruplex‐based sensing platforms for enzyme activity. The highlighted studies showcase the versatility of the G‐quadruplex motif for developing sensing assays for a variety of different enzymes.